Polygyny and HIV/AIDS: a health and human rights approach - Kelly, L. M. (Faculty of Law, University of the Free State, 2006)
Concurrent sexual networks have been identified in empirical studies as significantly amplifying rates of HIV transmission in comparison to sequential monogamy or sporadic sexual encounters. This paper examines how states’ legal condonation of discriminatory, high-risk concurrent sexual networks, including polygyny, violates women’s human rights and undermines their sexual and reproductive health. Because of its gender asymmetry and aggravation of marital inequality, polygyny places women at a greater risk of HIV infection and restricts their ability to insist on partner fidelity, negotiate condom use and leave high-risk relationships. The continued legal recognition of polygyny at the point of marriage formation by the majority of Southern African states violates women’s equality, health, and dignity rights. This paper stresses states’ international obligations to cease deferring to parallel legal systems that perpetuate inequality within marriage and family life. In moving to discourage polygyny, this paper posits an engagement approach that would continue to protect women’s rights within existing unions while discouraging the practice at the point of marriage formation. Going forward, HIV prevention programmes can provide useful fora to advance social justice and equality within marriage and intimate relationships when they are evidence-based and respond to the diverse realities of women’s lived sexual and marital experiences. Programmes that address social constructions of gender and sexuality will likely prove the most effective in discouraging polygyny and advancing transformative gender equality.

Daar is in empiriese studies uitgewys dat konkurrente seksuele netwerke die koerse van MIV-oordrag betekenisvol verhoog in vergelyking met voortvloeiende monogamie of sporadiese seksuele ontmoetings. Hierdie referaat ondersoek hoe state se regskondonasie van diskriminerende, konkurrente seksuele netwerke van hoë risiko, insluitende poliginie, vroue se menseregte skend en hul seksuele en reproduktiewe gesondheid ondermyn. As gevolg van die geslagsongelykmatigheid daarvan en die verergering van huweliksongelykheid, plaas poliginie vroue voor ’n groter risiko van MIV-infeksie en beperk dit hul vermoë om aan te dring op getrouheid van die lewensmaat, om te onderhandel vir die gebruik van kondome en om hoërisikoverhoudings te laat vaar. Die voortgesette regserkenning van poliginie by die punt van huweliksvorming deur die meerderheid van state in Suider- Afrika, skend vroue se gelykheids-, gesondheids- en waardigheidsregte. Hierdie referaat beklemtoon state se internasionale verpligtinge om op te hou om parallelle regstelsels in ag te neem wat ongelykheid binne huwelike en gesinslewe in stand hou. In ’n poging om poliginie te ontmoedig, stel hierdie referaat ’n benadering van betrokkenheid voor waar daar voortgegaan sal word om vroueregte te beskerm binne bestaande verbintenisse, terwyl die praktyk ontmoedig sal word by die punt van huweliksvorming. Om vorentoe te beweeg kan MIV-voorkomingsprogramme bruikbare forums verskaf om sosiale geregtigheid en gelykheid binne die huwelik en intieme verhoudings te bevorder wanneer hul getuienisgebaseerd is en op die diverse realiteite van vroue se geleefde seksuele en huwelikservaringe reageer. Programme wat sosiale konstruksies van geslag en seksualiteit aanspreek sal waarskynlik bewys dat dit die effektiefste is in die ontmoediging van poliginie en die bevordering van transformerende geslagsgelykheid.
Keywords: HIV/AIDS; Polygyny; Women’s human rights; Sexual health; Reproductive health; Gender equality